FEATURES OF ACCOUNTING THE RISK FACTOR IN THE MANAGEMENT OF INNOVATION PROJECTS - PYLYPIAK, Oleksandr; BAKAY, Vitaliy; SACHYNSKA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
It is shown that the problem of taking into account the risk factor in the management of innovation projects is acquiring a new sound and a qualitatively new level of relevance today. Under martial law, the economic system functions in special conditions of turbulence, when, on the one hand, it is difficult to talk about efficiency without innovation, and on the other hand, it is necessary to apply new approaches to managing innovation projects, since the standard methods developed no longer work properly. The essence of the basic approaches to taking into account the risk factor in the management of innovation projects is considered. The problems of risk assessment in decision-making on innovative projects are highlighted. The conditions for the influence of risks on innovative decisions for the pre-investment, investment and post-investment phases are shown. The relationship between risk and return for alternative innovative projects and a specific innovative project is reproduced. The conditions for the emergence of risks and uncertainty in the economic system are separately characterized. The factors that contribute to the manifestation of uncertainty in the management of innovation projects are systematized. The article provides a classification of project losses, in particular, additional project costs in excess of the planned ones, project costs that do not bring the expected effect and losses due to lost opportunities. One of the possible options for positioning project losses in three-dimensional space through such elements as the zone of unacceptable losses, the zone of undesirable losses, the zone of acceptable losses, and the zone of planned losses is presented. One of the common options for identifying risks through the search for the overall risk of an innovative project is reproduced. It is shown that further research on project risk in the field of innovation project management should be carried out in the plane of applying the mathematical apparatus to describe the factors-causes and factors-consequences of risks.